Combined antifogging and antireflective double nanostructured coatings for LiDAR applications - Gaertner, Anne; Sabbagh, Ahmad; Schulz, Ulrike; Rickelt, Friedrich; Bingel, Astrid; Wolleb, Sabrina; Schroeder, Sven; Tuennermann, Andreas (Applied Optics, 2023)
To increase the performance of optical systems, a good antireflective coating is required to ensure low reflectance and high transmittance of optical surfaces. Further problems, such as fogging that causes light scattering, negatively affect the image quality. This implies that other functional properties are also required. Presented here is a highly promising combination of an antireflective double nanostructure on top of an antifog coating with long-term stable properties, generated in a commercial plasma-ion-assisted coating chamber. It is demonstrated that the nanostructures do not affect the antifog properties and can be successfully used for many applications.
CRIS-Team Scopus Importer:2023-04-20